Breast cancer beliefs and screening behaviors among South Asian immigrant women living in the United States - Racquel E. Kohler; Tina Dharamdasani; Jacelyn Tarn; Myneka Macenat; Jeanne M. Ferrante; Shailja Mathur; Elisa V. Bandera; Anita Y. Kinney; Jaya M. Satagopan (BMC Women's Health)
Abstract Background Breast cancer incidence is increasing among South Asian women in the United States (US). This qualitative study explored breast cancer beliefs, behaviors, and experiences among South Asian immigrant women in New Jersey (NJ). Methods We conducted four online focus groups with South Asian women from NJ, aged ≥ 25 years with no prior history of cancer, in English, between June 2021 and July 2022. Thematic content analysis was guided by the Social Contextual Framework. Results We recruited 22 participants, average age 52 (standard deviation (SD) = 8.4) years, all born in South Asia, and living in the US for an average of 26 (SD = 11.7) years. Low perceived individual risk of breast cancer was influenced by no family history and healthy lifestyles. Despite diet changes since immigrating and misconceptions held by some, women understood the benefits of mammography. Interpersonal and cultural barriers included family responsibilities and norms deprioritizing women’s health and health-seeking behaviors. Access to care may be limited by structural factors including immigration status, insurance, and language barriers. Social norms regarding stigma, modesty, and self-disclosure may vary by generation and context. Conclusions Despite low perceived breast cancer risk and some cultural and structural barriers to screening, South Asian immigrant women generally understood mammography’s early detection benefits. Culturally appropriate interventions leveraging family ties and social networks are needed to dispel misconceptions, promote health-seeking behaviors, and address structural barriers.